Classification of puck possession events in ice hockey - Tora, M. R.; Chen, J.; Little, J. J. (IEEE/CVF Conference on Computer Vision and Pattern Recognition, 2017)
Group activity recognition in sports is often challenging due to the complex dynamics and interaction among the players. In this paper, we propose a recurrent neural network to classify puck possession events in ice hockey. Our method extracts features from the whole frame and appearances of the players using a pre-trained convolutional neural network. In this way, our model captures the context information, individual attributes and interaction among the players. Our model requires only the player positions on the image and does not need any explicit annotations for the individual actions or player trajectories, greatly simplifying the input of the system. We evaluate our model on a new Ice Hockey Dataset. Experimental results show that our model produces competitive results on this challenging dataset with much simpler inputs compared with the previous work.